The Efficacy of Fucoidan on Gastric Ulcer - Mohammad Juffrie; Ina Rosalina; Wahyu Damayanti; Ali Djumhana; A. Ariani; Harjono Ahmad (Universitas Gadjah Mada, 2006)
Hyperacidity causes gastric injury, and in severe situations, ulcer could develop. The growth factors known asthe basic fibroblast growth factor (bFGF) and the epidermal growth factor (EGF) have been recognized to promoteulcer healing. Fucoidan is extracted from a brown seaweed of Okinawa called Mozuku or Cladosiphon okamuranus.Fucoidan is effective for the healing of gastric ulcers by inducing epithelial cells to produce growth factors. The aimof this study is to explore the efficacy of fucoidan in patient who suffered by gastric ulcer. A randomized control trialdouble blind was conducted to 33 eligible samples. By using four-blocks random samples were divided into fucoidanand placebo groups. 100 mg of fucoidan was given to the fucoidan group and 100 mg of glucose was given to theplacebo group. Due to ethical reasons, for both groups were given a proton pump inhibitor. There was no differencein the age category between the fucoidan group (mean: 46.23 ± 14.8 years) and the placebo group (mean: 46.18 ± 18.4years) (p: 0.28). There was also no difference in sex between the fucoidan group (female: 10/33; male 7/33) and theplacebo group (female: 7/33; male: 9/33); p: 0.38. According to the SAKITA and MIWA criterias 32 patients fulfilledA1 which indicate active severe ulcer, and 1 patient fulfilled A2 which indicate active moderate ulcer. Most of theulcers were gastric ulcer. There was a significant improvement of the grade of ulcer in fucoidan group (94%) (16/17)compared to placebo group (37.5%) (6/16,p: 0.005). There was a significant reduction of abdominal pain after 5 daysin the fucoidan group, compared to the placebo group (p: 0.04). Vomiting tends to decrease in day 6 of the fucoidangroup however its proportion is similar with that of the placebo group (p: 0.9). Fucoidan is effective for ulcer healingand reducing ulcer symptoms.Key words : fucoidan, gastric ulcer, anti-peptic activity